2022
DOI: 10.1001/jamanetworkopen.2022.25331
|View full text |Cite|
|
Sign up to set email alerts
|

Duration of Symptoms and Association With Positive Home Rapid Antigen Test Results After Infection With SARS-CoV-2

Abstract: releasing culture-positive, potentially infectious individuals prematurely, underscoring the importance of proper mask wearing and avoidance of high-risk transmission venues through day 10.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…All patients were clinically recovered at discharge, but one (2.9%) was transferred to hospital due to intractable fever. The median time between admission and discharge was 10 days (range, [5][6][7][8][9][10][11][12][13][14]. The median value of viral load at diagnosis was 18.2, and the majority of cases (73.5%) were Delta variants.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All patients were clinically recovered at discharge, but one (2.9%) was transferred to hospital due to intractable fever. The median time between admission and discharge was 10 days (range, [5][6][7][8][9][10][11][12][13][14]. The median value of viral load at diagnosis was 18.2, and the majority of cases (73.5%) were Delta variants.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the RAT-positive rate gradually decreased over time after symptom onset. At the time of this writing, Cosimi et al reported that RAT has a high negative predictive value (100%), so a negative RAT result could provide reassurance in ending isolation ( 8 ). Our findings of high negative predictive value of a negative RAT are consistent with this study ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although antigen test positivity correlates well with culture positivity and higher viral loads [ 3–7 ], it is not a perfect proxy. A study by Cosimi et al found that only half of participants with a positive antigen test had a positive viral culture on day 6 following symptom onset [ 18 ]. Interestingly, that study, and another by Bouton et al, both report 100% negative predictive values for antigen testing with relationship to culture positivity [ 16 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study by Cosimi et al found that only half of participants with a positive antigen test had a positive viral culture on day 6 following symptom onset [ 18 ]. Interestingly, that study, and another by Bouton et al, both report 100% negative predictive values for antigen testing with relationship to culture positivity [ 16 , 18 ]. Those studies provide reassuring data that those with a negative antigen test on day 6 are unlikely to be shedding viable virus.…”
Section: Discussionmentioning
confidence: 99%